Innovative System for Animal Waste Utilization Using Closed-Loop Material and Energy Cycles and Bioenergy: A Case Study - Zygmunt Kowalski; Agnieszka Makara (Energies)
This study proposes an innovative model for animal waste utilization in the largest Polish meat utilization plant, which assumes an integrated system that processes one part of the meat waste by anaerobic digestion and the second part into meat and bone meal via the hydrothermal method. The solution is based on implementing the concept of industrial symbiosis, using a purposefully directed flow of materials, waste, and energy to create a closed recycling cycle. This study analyzes the key strategic, organizational, and technical circular economy activities that enable the transformation of waste into valuable materials and energy, thanks to the use of closed-loop materials and energy cycles. It estimates the integrated system’s investment costs and economic and environmental outcomes. The presented method allows for biogas production from the bio-fermentation of 160,000 t/y of animal waste; this would more than cover the heat requirements for obtaining 110,000 t/y of meat and bone meal using the hydrothermal method.